The Next-generation Biomass for Biorefining - Hah Young Yoo; Seung Wook Kim (BioResources, 2021)
Biorefining, which uses biomass as feedstock and converts it into valuable products, is a core technology for the sustainable green industry and has high potential as an alternative to the current petrochemical-based industry. This article covers the requirements for feedstock that should be met for the economic feasibility of a biorefinery. In particular, organic waste that meets several requirements as the next-generation biomass has high potential. However, the complex and significant differences in composition depending on the origin make it difficult to follow the previous system of classification such as cellulose, hemicellulose, and lignin. In particular, several organic wastes contain high value-added bioactive components. Therefore, a strategy for the effective use of high value-added ingredients contained in trace amounts is required, which is briefly introduced in the third section of this article.